Digital Transformational Leadership: A Bibliometric Study of Digital Transformation Trends, Themes, and Challenges in Organizations - Kismiadi, Kismiadi; Firdaus, Rahmad; Suhardi, Suhardi (Economic: Journal Economic and Business, 2025)
Digital transformation has become the centre of attention in modern organizational strategies, especially in the context of digital transformational leadership. This research aims to map the intellectual structure and global research trends related to these themes through a bibliometric approach. Data were obtained from the ScienceDirect database using the keyword "digital transformational leadership" and coverage of the publication years 2020 to 2025. A total of 500 articles that met the inclusion criteria were analyzed using the VOSviewer software. The visualization results show five main clusters that are interconnected, namely digital leadership, digital competence, digital innovation, barrier to transformation, and sustainable performance. Digital leadership emerged as a central theme, while barriers and technostress became a new issue that developed in the latest literature trends. The visual overlay analysis also shows a shift in focus from the technological aspect to the strategic and human resources aspect. This research makes a theoretical contribution in identifying the direction and opportunities for advanced research in the field of digital leadership, as well as practical implications for organizations in sustainably managing digital transformation. This study also emphasizes the importance of digital competence, continuous innovation, and mitigation of technological barriers as the foundation for organizational success in the era of digital disruption.